(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the significant effect on students’ science learning outcomes with the make a match type of cooperative learning model. This study is a quantitative study with a Quasi Experimental Design and uses a Nonequivalent Control Group research design, which means the control sample is not selected randomly. This study used a sample of 17 students of class VI A as the experimental class and 17 students of class B as the control class. Data collection techniques used were observation, interviews, student needs questionnaires, and pre-test and post-test instruments. The test instrument trial was tested using a validity test, a reliability test, a difficulty level test, and a discriminatory power test. Pre-test and post-test data were tested using a normality test with a split half technique, Levene’s homogeneity test and an independent sample t-test hypothesis test. Based on the result of the Independent sample t-test data analysis on the post-test obtained a significant value of 0.000, according to the criteria that the 2-tailed significance value < 0.05, then Ho is rejected and Ha is accepted. The results of the hypothesis test show that there is a significant difference in the effect of the application of the make a match type cooperative learning model on the science learning outcomes of class VI students of UPTD SD Negeri Kraton 1 Bangkalan.